ETHNOMATHEMATICS: LEARNING GEOMETRY FROM BANYUMAS BATIK PATTERNS - Fitria Zana Kumala; Arsa Nur Tsabitah (Yayasan Education and Social Center, 2022)
Ethnomathematics is a science used to express the relationship between culture and mathematics. Banyumas Regency has a variety of cultures, one of which is batik Banyumas. Batik Banyumas have a characteristic black base color with light color patterns or scribbles, and designs from batik Banyumas contain elements of flora and fauna in Banyumas. This study aims to discover the mathematical concept in batik Banyumas and how to analyze these mathematical concepts. This research is qualitative research with an ethnographic approach. The data collection process carries out by documentation. Data analysis uses data collection methods, data reduction, presentation, and drawing conclusions and verification—data validity technique using source triangulation. The mathematical concepts identified in Batik Banyumas are the concept of points, line segments, flat constructs (isosceles triangles, parallelograms, rectangles, rhombuses, and circles), congruence and similarity, as well as geometric transformations (translation, reflection, dilatation, and rotation). The results of this study can be used as a reference for teachers in the application of contextual learning related to learning resources that come from the environment around students and as an explanation to students that mathematics learning can connect to the culture around students, namely the batik Banyumas